Learning path : professional Java developer (LiveLessons., 2016)
"Written for programmers with a background in high-level language programming, this LiveLesson applies the Deitel signature live-code approach to teaching programming and explores the Java language and Java APIs in depth. The LiveLesson presents concepts in the context of fully tested programs, not code fragments. The LiveLesson features hundreds of complete Java programs with thousands of lines of proven Java code, and hundreds of tips that will help you build robust applications."--Resource description page.